Developmental validation of the DNATyper™Y26 PCR amplification kit: An enhanced Y-STR multiplex for familial searching. (January 2019) - Mo, Xiao-Ting; Zhang, Jian; Ma, Wen-Hua; Bai, Xue; Li, Wan-Shui; Zhao, Xing-Chun; Ye, Jian
Highlights: The DNATyper ™ Y26 PCR Amplification kit, which including 26 low-medium mutating Y-STRs, is designed for Y-STR familial searching casework. The kit combines nine new Y-STR loci in addition to the 17 Y-STR loci from the commercially available AmpFlSTR ® Yfiler ® kit. Compared to the YFiler ™ kit, the DNATyper ™ Y26 kit contains nine new low-medium mutation Y-STR loci and increased the forensic discrimination from 92.19 to 98.69%. Abstract: The DNATyper ™ Y26 PCR Amplification kit, which including 26 low-medium mutating Y-STRs, is designed for Y-STR familial searching casework. The kit combines nine new Y-STR loci in addition to the 17 Y-STR loci from the commercially available AmpFlSTR®Yfiler® kit. The validation of the DNATyper ™ Y26 kit was performed in terms of technical index, including accuracy, stability, species specificity, sensitivity, adaptability for various samples, and mixture. Further, mutations of the 26 Y-STRs were analyzed by 1167 DNA-confirmed father-son pairs, and the results indicated that these loci had low or medium mutation rates. Furthermore, these Y-STRs loci were also tested in 1072 random male samples from Henan, Shanxi, Inner Mongolia, and Chongqing in China, showing their high power for forensic discrimination in the Chinese population. Thus, the DNATyper ™ Y26 PCR Amplification kit is a powerful tool for 'Y-STRs familial searching' in actual sexual-assault cases, indicating its unique advantage in familial searching due to Y-STR loci with only low-medium mutation rates.